A transformed fixed effect stochastic frontier approach for productivity evaluation in Indian electricity sector. Issue 9 (19th November 2018) - Khetrapal, Pavan
Abstract : Purpose: The purpose of this paper is to evaluate the utility-level productivity changes in Indian electricity sector during a period that witnessed structural reforms through several landmark regulatory changes. Design/methodology/approach: A transformed fixed-effect stochastic frontier panel approach accounting for time-invariant unobserved heterogeneity is employed to evaluate the productivity changes, and the inefficiency level in 98 utilities spanning over the years 2001–2010. A flexible translog production model is modeled and estimated, and decomposition of productivity into components of changes in efficiency, scale technology and price effect is computed. Findings: The empirical findings obtained from the present study suggest that the utility-level productivity in Indian electricity sector has generally declined during the observed period of 2001–2010 specifically after the implementation of Electricity Act 2003. Also, it is estimated that the state-level un-bundling of the electricity sector is not significantly associated with utility-level efficiency change. Furthermore, efficiency improvements attributable to increased competition are observed only in the case of smaller gas-based generating utilities. Originality/value: Earlier studies on the productivity evaluation of Indian electricity industry have applied the non-parametric data envelopment analysis approach, which has several limitations. The novelty of the paper lies in the fact that this paper is one of the first attempts that implement transformed fixed-effect stochastic frontier panel approach and thus disentangle unobserved heterogeneity from inefficiency. Furthermore, it is the only paper that analyzes 98 utilities (51 generating utilities, 38 transmission and distribution licensees and 9 vertically integrated utilities) in a single framework during the period 2001–2010.